Anesthetic Management of Transoral Odontoidectomy in a Child with Multiple Drugs Intolerance Syndrome - Ajayan, Neeraja; Hrishi, Ajay P.; Divakar, Ganesh (Journal of Neuroanaesthesiology and Critical Care, 2023)
Patients with an adverse reaction to more than three groups of drugs have multiple drug intolerance syndrome (MDIS). Regional anesthesia can be an attractive alternative when patients presenting for surgery are diagnosed with MDIS for opioids and nonsteroidal anti-inflammatory drugs (NSAIDs). Moreover, supplementary regional anesthetic techniques reduce exposure to multiple anesthetic medications, reducing the incidence of allergic reactions. We report the case of a pediatric patient diagnosed with MDIS presenting for transoral odontoidectomy and tracheostomy, wherein regional anesthesia techniques aided us in providing perioperative analgesia and maintaining hemodynamic stability.
Keywords: multiple drug intolerance syndrome; regional anesthesia; transoral odontoidectomy